Genetic Diversity of Iraqi Barley Species Differing in Their Tolerance to Drought by RAPD Analysis - Nidhal N. Hussain; Zainab R. jassem; Harb Adeel (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The genetic diversity was studied in sixteen barley Hordeum vulgar L. species cultivated in Iraq , which are differ in their ability to drought stress tolerance by using random amplified polymorphic DNA polymerase chain reaction (RAPD - PCR ) .Barley species was evaluated to drought stress  after treatment the plant seedling at germination stages to different concentration of polyethylene glycol (PEDG6000) . The results showed that the Broaq and Arefat species have the highest tolerance to drought stress in contrast the rest of Barly species like Alkhair, Alwarkaa, Ebaa99, Shoaa, Alrafidain,Sameer Rehana 3 , forat9 , jazeral ,and ebaa7 revealed sensitivity to drought stress .      The primes which used RAPD technique for all the studied species were produced 203 bands . The percentage of monomorphic bands is 10.39 % , while the polymorphic bands scored 89.70% raning from 71.4 % for OP-B11 primer to 100% for OP-C16 primer .Some primers produced specific or distinguished bands for some Barley species , such as primer OP-N13 which produced band with 450 bp molecular weight. and this band was   appeared in sensitive drought stress species only like Forat 9 ,Jazera 1 and Ebaa7. Primer P27 produced band with 2000 bp molecular weight and this band was appeared in highest tolerance Boraq Barley species .This band maybe associated with drought tolerant.   Cluster analyses by using jaccard scale for genetic similarity revealed a dendogram with three major groups with 75% similarity degree .The first and second sub group of group one included the tolerant and moderately tolerant species excluding Alkhair and Alwarkaa species which they are separated according to their genetic origin with one of the parents (Arefat) . The second and the third groups with the third sub group of group one included the sensitive species. The results of RAPD markers indicated the presence of high percentage of genetic diversity within the studies Barley species cultivated in Iraq .Moreover .these result enable the researches to separate the samples which differ in their ability to drought stress tolerance by using few numbers of genetic sites.